2022
DOI: 10.51847/fi0drot286
|View full text |Cite
|
Sign up to set email alerts
|

Temporomandibular Disorders: A cross Sectional Study into the Knowledge and Awareness Among Saudi Arabian Population

Abstract: Temporomandibular disorder (TMD) is a group of clinical troubles and is considered one of the major causes of non-dental pain. TMD is characterized by a wide range of signs and symptoms associated with TMJ and other related structures that negatively affect the Quality of life (QoL). This study investigated the public knowledge about TMD among people living in the Kingdom of Saudi Arabia's main cities and provinces. An electronic survey was designed, containing 16 questions in Arabic and English. The survey wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
0
0
Order By: Relevance
“…In a study conducted in Saudi Arabia, the level of public knowledge about TMD was assessed and it was found that 22.7% of the participants chose dentists and 74.5% chose medical doctors as the qualified specialists for TMD treatment. In their study, the available survey data revealed that there was insufficient knowledge about TMD, and they emphasized the need for educational seminars to increase public awareness of TMD (16).…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted in Saudi Arabia, the level of public knowledge about TMD was assessed and it was found that 22.7% of the participants chose dentists and 74.5% chose medical doctors as the qualified specialists for TMD treatment. In their study, the available survey data revealed that there was insufficient knowledge about TMD, and they emphasized the need for educational seminars to increase public awareness of TMD (16).…”
Section: Discussionmentioning
confidence: 99%
“…Temporomandibular disorders (TMDs) are a group of diseases that affect the masticatory muscles, the temporomandibular joints (TMJs), and the structures around them [1]. The "craniocervical-mandibular system," which consists of the temporomandibular joint, the masticatory muscles, and ligaments connecting the temporomandibular joint and the cervical region, is a functional unit that has yet to be fully understood [2]. However, this biomechanical interaction may play a role in the functional reliance between the cervical and masticatory systems [3].…”
Section: Introductionmentioning
confidence: 99%